2022
DOI: 10.1155/2022/5439023
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Study on the Relationship between the Expression of m6a-Related Genes and the Prognosis and Immunotherapy of Soft Tissue Sarcoma

Abstract: Background. Soft tissue sarcomas (STS) are rare malignancies arising from mesenchymal tissue and interlacing ectodermal nerve tissue. Immunotherapy plays an important role in the prognosis and survival of STS patients. However, there is insufficient evidence to confirm the prognostic value of m6A-related genes and to evaluate the efficacy of immunotherapy for STS. Methods. We analyzed 23 m6A regulators from STS samples using R software and defined the modification patterns for three STS m6A regulators. Then, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Qiu and Bae et al evaluated the expression of immune biomarkers in STS and found that increased CTLA4, PD-1, and LAG3 were connected to a good prognosis. [ 55 , 56 ] This result also indicated that STS patients who respond well to immunotherapy have higher pyroptosis scores, higher levels of immune cell infiltration, and stronger immune surveillance and immune-killing effects on tumor cells, which can explain the results of better OS in STS patients with high pyroptosis scores. Therefore, due to the prognosis prediction and the guidance for the immunotherapy strategy and targeted therapy program, the pyroptosis score might significantly benefit STS patients.…”
Section: Discussionmentioning
confidence: 77%
“…Qiu and Bae et al evaluated the expression of immune biomarkers in STS and found that increased CTLA4, PD-1, and LAG3 were connected to a good prognosis. [ 55 , 56 ] This result also indicated that STS patients who respond well to immunotherapy have higher pyroptosis scores, higher levels of immune cell infiltration, and stronger immune surveillance and immune-killing effects on tumor cells, which can explain the results of better OS in STS patients with high pyroptosis scores. Therefore, due to the prognosis prediction and the guidance for the immunotherapy strategy and targeted therapy program, the pyroptosis score might significantly benefit STS patients.…”
Section: Discussionmentioning
confidence: 77%
“…Studies had demonstrated that the expression of m6A-related genes was closely related to the immune microenvironment of malignant tumors and can guide patient immunotherapy ( 23 ). Meanwhile, m6A genes were mainly enriched in the formation of extracellular traps in neutrophils, suggesting that probing the m6A patterns of tumors can help to understand the diversity and complexity of the tumor microenvironment ( 23 ). It has been shown that models that integrate multiple markers into a single model outperform those constructed using a single marker, facilitating individualized patient management ( 24 ).…”
Section: Introductionmentioning
confidence: 99%